Meningkatkan kemampuan pengenalan keaksaraan dan percaya diri Pada Anak Kelompok A Melalui Pengembangan Media Buku Aktif POP UP berbasis flipchart di TK. NEGERI BUNG KARNO - Widya Nurkayatin; Rachma Hasibuan (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
This study aims to get a solution to the problem of difficulty in improving language skills in terms of early reading in early childhood in group A1 in di Negeri Bung Karno surabaya. The research method used in this study, is a research and development method or often referred to as Research and Development (R & D), The subject of this study is students of group A1 of di Negeri Bung Karno surabaya Kindergarten for the 2023-2024 academic year with a total of 12 students with an average age of 4-5 years, consisting of 4 female students and 9 male students.The results of the study conveyed data on the difference between the use of Flipchart-based Pop Up learning media with an increase in initial reading skills in the A1 group of di Negeri Bung Karno Kindergarten Surabaya. From the table above, the result tcalculate = - with a significance level of 0.000. Because the significance level is less than 0.05, Ha is accepted, and Ho is rejected.Based on the results of this study, it can be concluded that "There is an effect of the use of Pop Up learning media on improving initial reading skills in group A1 children of di Negeri Bung Karno Kindergarten Surabaya"